Studi Dampak Kontrasepsi Suntik terhadap Akseptor Puskesmas Antang Perumnas Antang dalam Kaidah al-Ḍarar Yuzāl - Jujuri Perdamaian Dunia; Askar Patahuddin; Edi Gunawan (Al-Mizan (e-Journal), 2020)
This study aims to determine the impacts of contraceptive injection for acceptor health centers Antang Perumnas of the al-Ḍarar Yuzāl rule. This type of research is the qualitative approach to field research. The results of this research show that firstly, the condition of acceptors in health centers of Antang Perumnas Manggala is quite diverse, acceptors in this region belong to the middle and lower economic classes with varying levels of religious understanding; secondly, two reasons cause family planning acceptors to inject, namely internal and external reasons with different impacts on their acceptors; thirdly, the application of al-Ḍarar Yuzāl's rule for the use of contraceptive injections has the following Islamic legal implications: wajib when the acceptor is awake from diseases such as uterine cancer, or death if having a pregnancy, becomes makruh if the acceptor feels pain during menstruation and intercourse, or the emergence of uterine myoma in the endometrium, and becomes haram when removing sexual sensitivity, not passionate until the feeling of anger towards the husband that ends in divorce. This research is expected to contribute to the medical world to find healthy birth control solutions for acceptors and make acceptors wiser before deciding to use contraceptive injection.